Urgensi Pendidikan Bias Implisit Bagi Hakim Untuk Mewujudkan Keadilan : Urgensi Pendidikan Bias Implisit bagi Hakim untuk Mewujudkan Keadilan - Aisyah Kahar (Ikatan Hakim Indonesia (IKAHI), 2025)
Implicit bias is an unconscious attitude or stereotype that influences understanding, actions and decisions. Therefore, it is possible that implicit bias can also affect the outcome of the decision made by the judge. This research is very useful to answer the importance of implicit bias education for a judge. This research uses normative legal research methods. The results show that implicit bias education is very important for judges as an effort to realize justice in their decisions so that it affects the level of public trust in the judiciary. In addition, mastery of implicit bias is also a form of transparency and overcomes concerns about bias and injustice. Involving the public and promoting a culture of openness also contributes to a more trustworthy and respected legal system.